2007
DOI: 10.1530/eje-07-0113
|View full text |Cite
|
Sign up to set email alerts
|

A novel mutation in the accessory DNA-binding domain of human steroidogenic factor 1 causes XY gonadal dysgenesis without adrenal insufficiency

Abstract: Objective: Steroidogenic factor 1 (SF1), officially designated NR5A1, is a nuclear receptor that plays key roles in endocrine development and function. Previous reports of human SF1 mutations revealed a spectrum of phenotypes affecting adrenal function and/or gonadal development and sex differentiation. We present the clinical phenotype and functional effects of a novel SF1 mutation. Patient: The patient is a 22-year-old 46, XY Japanese patient who presented with dysgenetic testes, atrophic vasa deferentia and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
39
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(47 citation statements)
references
References 31 publications
7
39
0
Order By: Relevance
“…First, interallelic association with the known p.Gly146Ala polymorphism (rs1110061) may further reduce NR5A1 activity and contribute to more severe phenotypes (WuQiang et al, 2003; Hasegawa et al, 2004; Wada et al, 2006; Reuter et al, 2007; Köhler et al, 2008; Lourenço et al, 2009; Bashamboo et al, 2010a; Paris et al, 2011; Camats et al, 2012). However, two patients in our cohort also bore the p.Gly146Ala variant besides the pathogenic NR5A1 variants, p.Trp302Cys and p.Tyr404*, and their phenotype was not strikingly distinct or more severe.…”
Section: Discussionmentioning
confidence: 99%
“…First, interallelic association with the known p.Gly146Ala polymorphism (rs1110061) may further reduce NR5A1 activity and contribute to more severe phenotypes (WuQiang et al, 2003; Hasegawa et al, 2004; Wada et al, 2006; Reuter et al, 2007; Köhler et al, 2008; Lourenço et al, 2009; Bashamboo et al, 2010a; Paris et al, 2011; Camats et al, 2012). However, two patients in our cohort also bore the p.Gly146Ala variant besides the pathogenic NR5A1 variants, p.Trp302Cys and p.Tyr404*, and their phenotype was not strikingly distinct or more severe.…”
Section: Discussionmentioning
confidence: 99%
“…So far, no clear genotype-phenotype correlation could be detected in patients with NR5A1 mutations. However, in patients with severe forms of 46,XY DSD, previously described mutations are mostly missense mutations in the DNA-binding region (including its accessory DNA-binding domain) or in the ligand-binding domain as well as nonsense mutations leading to severe changes of the protein (8,10,16,21,30,31,32,33,36,37,38,39).…”
Section: European Journal Of Endocrinologymentioning
confidence: 99%
“…The second mutation was a homozygous missense mutation (R92Q) that disrupts the A-box secondary DNA binding domain [7]. However, recent several studies have demonstrated that heterozygous mutations are more frequently identified in 46, XY disorders of sex development (DSD) patients without adrenal failure rather than in 46, XY DSD patients with adrenal failure [3,[9][10][11][12][13][14][15][16][17]. Therefore, the testis is likely to be more sensitive to partial loss of SF-1/Ad4BP function than the adrenal gland in human.…”
mentioning
confidence: 99%